Study on a Welding Device with Automatic Capture Used in Rolling Welder for Steel Bar Cage - Wang Demin; Cheng Yang; Wang Shukun (Jixie chuandong)
In order to improve the efficiency of rolling welder for steel bar cage,a welding machine with capturing and tracking is proposed,considering the motion characteristics of solder joints formed by the joint of stirrup and the main reinforcement. The device includes two parts,which control the movement of the vertical and horizontal direction of the welding torch. The pneumatic control mode is used to control the motion of the welding torch in the plane with the interaction between the induction switch and touch panel. The device has the characteristics of automatic capture to the solder joint,and it can also track the solder joint after the capture,the automatic level and production efficiency of the steel bar cage welding is improved.